Belajar Dari Rumah Menggunakan Metode Problem Based Learning dengan Google Jamboard - Heti Nurida Munawati (LPMP Provinsi DKI Jakarta, 2021)
Online learning during the covid pandemic has challenges in active learning for students. This study aims to determine the activeness of learning science students during Learning From Home using the Problem Based Learning method with Google Jamboard. and implemented using two cycles, each consisting of four stages, namely planning, implementation, observation and reflection. Data collection techniques are carried out through observation during the activity and monitoring of the work in the form of photos of the results of the activities uploaded to Google Jamboard. From the results of the study, it can be concluded that there is an increase in science learning activity using the Problem Based Learning method with Google Jamboard in science lessons in Learning From Home conditions, meaning that online learning has the potential to be developed in subjects with the same character.